2011
DOI: 10.1142/s0219519411004113
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties of Extensor Tendon Repair Using the Six-Strand Single-Loop Suture Technique: A Comparative Analysis With Three Other Techniques in Cadaveric Models

Abstract: A six-strand single-loop technique has been implemented for repairing extensor tendons. This paper describes an investigation to compare the biomechanical properties of extensor tendons repaired using this technique with three other commonly used techniques, namely the Kessler-Tajima (two-stand) technique, the Tsuge (two-strand) technique, and the modified (four-strand and double-loop) Tsuge technique. Epitendinous stitches were implemented on all techniques. From human cadaveric hands, extensor tendons were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, that study found a significant decrease in resistance of PGA after remaining from 5 to 7 days in the mouth. In contrast to these results, Lim and coworkers [ 16 ] studied the biomechanical properties of a nonabsorbable braided suture, Supramid, with three different suture techniques. The authors concluded that the six-strand single-loop suture technique, pulls out, rather than breaking, at sufficiently high loads and let tissues transfer large forces along the suture.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study found a significant decrease in resistance of PGA after remaining from 5 to 7 days in the mouth. In contrast to these results, Lim and coworkers [ 16 ] studied the biomechanical properties of a nonabsorbable braided suture, Supramid, with three different suture techniques. The authors concluded that the six-strand single-loop suture technique, pulls out, rather than breaking, at sufficiently high loads and let tissues transfer large forces along the suture.…”
Section: Discussionmentioning
confidence: 99%